Development and virucidal activity of a novel alcohol-based hand disinfectant supplemented with urea and citric acid. Issue 1 (December 2016) - Ionidis, Georgios; Hübscher, Judith; Jack, Thomas; Becker, Britta; Bischoff, Birte; Todt, Daniel; Hodasa, Veronika; Brill, Florian; Steinmann, Eike; Steinmann, Jochen
Abstract Background Hand disinfectants are important for the prevention of virus transmission in the health care system and environment. The development of broad antiviral spectrum hand disinfectants with activity against enveloped and non-enveloped viruses is limited due to a small number of permissible active ingredients able to inactivate viruses. Methods A new hand disinfectant was developed based upon 69.39 % w/w ethanol and 3.69 % w/w 2-propanol. Different amounts of citric acid and urea were added in order to create a virucidal claim against poliovirus (PV), adenovirus type 5 (AdV) and polyomavirus SV40 (SV40) as non-enveloped test viruses in the presence of fetal calf serum (FCS) as soil load. The exposure time was fixed to 60 s. Results With the addition of 2.0 % citric acid and 2.0 % urea an activity against the three test viruses was achieved demonstrating a four log10 reduction of viral titers. Furthermore, this formulation was able to inactivate PV, AdV, SV40 and murine norovirus (MNV) in quantitative suspension assays according to German and European Guidelines within 60 s creating a virucidal claim. For inactivation of vaccinia virus and bovine viral diarrhea virus 15 s exposure time were needed to demonstrate a 4 log10 reduction resulting in a claim against enveloped viruses. Additionally, it is the first hand disinfectant passing a carrier test with AdV and MNV. Conclusions In conclusion, this new formulation with a low alcohol content, citric acid and urea is capable of inactivating all enveloped and non-enveloped viruses as indicated in current guidelines and thereby contributing as valuable addition to the hand disinfection portfolio.